2020
DOI: 10.1093/icesjms/fsaa033
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing triple bottom line harvest strategies

Abstract: Over the past 50 years, the diversity of fisheries types being actively managed has changed from mainly data-rich, industrial sectors to more socially, economically, and environmentally complex multispecies and multisector fisheries. Accompanying this change has been a broadening of management objectives to include social and economic considerations with traditional resource sustainability objectives, the so-called triple bottom line, and the need to include these considerations into harvest strategies. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…social, ecological and economic objectives) and recognising the issues that face all fishing interests (e.g. commercial, recreational, charter, conservation and traditional fishing) (Brownscombe et al 2019;Dichmont et al 2020). Underlying these complex challenges are the inherent complications associated with working at the political interface, and how alternative arrangements such as nonregulatory, co-management frameworks and harvest strategies can be used to generate better outcomes (Nursey-Bray et al 2018).…”
Section: Theme 1: Biosecuritymentioning
confidence: 99%
“…social, ecological and economic objectives) and recognising the issues that face all fishing interests (e.g. commercial, recreational, charter, conservation and traditional fishing) (Brownscombe et al 2019;Dichmont et al 2020). Underlying these complex challenges are the inherent complications associated with working at the political interface, and how alternative arrangements such as nonregulatory, co-management frameworks and harvest strategies can be used to generate better outcomes (Nursey-Bray et al 2018).…”
Section: Theme 1: Biosecuritymentioning
confidence: 99%
“…Stahel 2016 ; Kirchherr et al 2017 ) Greater emphasis on environmental impacts in triple-bottom-line accounting, in conjunction with financial mechanisms, to support and rebuild marine ecosystems (e.g. Bos et al 2015 ; Dichmont et al 2020 ) Capacity-building in under-resourced communities decreases regional inequalities in development and implementation of integrated spatial management (Alvarez-Romero et al 2018 ; IOC-UNESCO 2017 ) Improved ecological monitoring and forecasting, and the transfer of such information, both of which enable more proactive, flexible, and adaptive management (e.g. Pendleton et al 2020 ) Improved monitoring, evaluation and adaptation of management strategies and plans (Ehler 2014 ; IOC-UNESCO 2017 ) Negotiations for a new UN BBNJ treaty have proceeded slowly (noting the effect of the coronavirus pandemic on the scheduling of conferences of the parties and intersessional activities) but seem increasingly likely to result in legally binding conservation obligations, and important States have indicated that they intend to ratify the treaty.…”
Section: Resultsmentioning
confidence: 99%
“…Greater emphasis on environmental impacts in triple-bottom-line accounting, in conjunction with financial mechanisms, to support and rebuild marine ecosystems (e.g. Bos et al 2015 ; Dichmont et al 2020 )…”
Section: Resultsmentioning
confidence: 99%
“…Many small-scale fisheries lack the capacity to mitigate global market forces and more international solutions are needed, such as development of insurance opportunities by international financial institutions (Knight et al, 2020). There has been an increase in the appreciation of the need to adopt triple bottom line approaches to fisheries management (Plagányi et al, 2013;Dichmont et al, 2020) but much more work is needed to ensure that supply chains are adaptable enough to ensure that the outlets for seafood products are maintained in the future. This is vital not only for economic stability, but also the livelihood and mental health of fishers, their socio-cultural wellbeing, and food and nutrition security globally (Hicks et al, 2019).…”
Section: Discussionmentioning
confidence: 99%